PEMFC voltage control using PSO-tunned-PID controller - Farhadi, P.; Sojoudi, T. (Proceedings of the 2014 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference : 3-5 February 2014, 2014)
This paper presents a PID control which is tuning by Particle Swarm Optimization to control the output voltage of the most-used fuel cell type, namely, Proton Exchange Membrane Fuel Cell (PEMFC). In this paper, PEMFC voltage is controlled for load changes in a simple study system. PID controller is used in control system for the fuel cell plant for these variations in terms of the input current into the membrane (I st ). The study plant tries to keep constant the output voltage of a fuel cell in the specific required amount. Simulations were carried out in MATLAB/SIMULINK environment. The obtained results verified the high performance capability of the proposed PSO-based tuning of a PID controller to achieve the mentioned goals.